2004
DOI: 10.1177/02601079x04001500305
|View full text |Cite
|
Sign up to set email alerts
|

The Socioeconomic Costs of Road Traffic Accidents in Ethekwini (Durban) Municipality, South Africa

Abstract: There were 51,880 road traffic accidents recorded in Durban Municipality in 1998, 46.4% being same direction accidents. Most of the casualties (38.8%) were from the vehicle/ pedestrian accidents. Casualties per 100 accidents were highest with vehicle/pedestrian accidents (97.5) and only 9.5 in same direction accidents. Fatalities occurred in 1% of the road traffic accidents and made up 5.1% of all casualties. The total costs of road traffic accidents in 1998 were US$151 million, which was 13.1% of the budget o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
6
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
4
6
1
Order By: Relevance
“…It was found that the present results are quite comparable with results from studies by other researchers. The higher preponderance of pedestrians is also been observed in other studies [20][21][22]. These findings categorize pedestrians and motorcyclist as the most vulnerable road users due to their lack of protection in the event of a crash.…”
Section: Discussionsupporting
confidence: 81%
“…It was found that the present results are quite comparable with results from studies by other researchers. The higher preponderance of pedestrians is also been observed in other studies [20][21][22]. These findings categorize pedestrians and motorcyclist as the most vulnerable road users due to their lack of protection in the event of a crash.…”
Section: Discussionsupporting
confidence: 81%
“…People in the 20-54 age group accounted for 71.8% of all those fatal cases annually [ 9 ]. The young population between ages of 20 and 34 is the age group mostly affected, and since is economically active, consequences overcome a person with wider implication on economic losses of their families also [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found in different studies, in the United Arab Emirates, driving behaviour are more prevailing contributing factors, and vehicle safety is least [ 11 ]. In South Africa, most of the casualties of road traffic accidents were drivers (46%) [ 10 ]. In Taiwan, human factor respectively psychosocial influences are responsible up 3 to 4% of accidents [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Road-traffic crashes still constitute a leading cause of premature deaths and a threat to the quality of life of the people of South Africa with more than 12,000 fatalities in 2003 (Brysiewicz, 2001;Olukoga, 2003Olukoga, , 2004a.…”
Section: Discussionmentioning
confidence: 99%
“…They are a major cause of morbidity and mortality comparable to HIV/AIDS, homicides and some chronic diseases in the country (Bradshaw et al, 2003;Brysiewicz, 2001;Olukoga, 2004a). Road-traffic crashes account for about 1% of the gross domestic product (GDP) of the country.…”
mentioning
confidence: 99%